INTEGRASI ANALISIS SPASIAL DAN SWOT UNTUK PENILAIAN POTENSI WISATA ALAM: STUDI KASUS KABUPATEN KUDUS - Eka Agustina, Vanny; Akbar Mukasyaf, Aziz; Dwi Priyono, Kuswaji; Tyas Pramono, Wahyu (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2025)
Nature-based tourism plays an important role in supporting regional economic growth, yet its management requires comprehensive spatial data–driven planning. This study analyzes the potential and development strategies of tourist attractions in Kudus Regency, Central Java, by combining spatial assessment methods and SWOT analysis. Data were collected through field observations, semi-structured interviews, open-ended questionnaires, and a review of planning documents. The assessment method was used to evaluate the attractiveness, accessibility, facilities, and community support of seven major tourist sites, which were then mapped spatially. The findings show that Rahtawu, Kali Banteng Waterfall, and Seribu Batu Semliro possess very high potential, whereas Hidden Canyon Rahtawu demonstrates very low potential. The SWOT analysis recommends development strategies based on tourism corridors, infrastructure improvement, digital promotion, and environmental conservation. These findings highlight the need for an integrated approach involving the government, community, and private sector to enhance destination competitiveness, extend tourist stays, and achieve sustainable tourism in Kudus Regency.